COLLABORATIVE LEARNING APPROACHES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article discusses cooperative learning methods and their importance in the educational process. The article discusses the main principles of cooperative learning, the possibilities of encouraging active participation of students, developing social skills and providing mutual support. Students' collaboration and exchange of ideas are emphasized through various forms such as group work, team projects, discussion and seminars. It also examines the role of teachers and changes in the educational process. The article highlights how cooperative learning methods can improve the quality of education and help students' personal development.